2017
DOI: 10.1007/s00467-017-3673-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of long-term renal function in survivors of childhood Wilms tumor

Abstract: Even though WT-S are believed to carry a low risk for end-stage renal disease, in this study, a remarkable number of WT-S presented with previously unidentified subclinical signs of renal function impairment and secondary morbidity. Therefore, it is important to continue regular follow-up, especially after transition into adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
0
35
0
1
Order By: Relevance
“…As per the UMBRELLA SIOP‐RTSG 2016 Wilms tumor protocol, nephron‐sparing surgery is acceptable in unilateral WT, providing at least 50% of renal tissue could be spared. In order to preserve as much renal tissue as possible and decrease renal and cardiac morbidity for long‐term survivors, nephron‐sparing surgery is always the preferred option 15,16 . MIS is appropriate only if the tumor has either a location (multiple small tumors, hilar tumor) or a volume that requires complete nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the UMBRELLA SIOP‐RTSG 2016 Wilms tumor protocol, nephron‐sparing surgery is acceptable in unilateral WT, providing at least 50% of renal tissue could be spared. In order to preserve as much renal tissue as possible and decrease renal and cardiac morbidity for long‐term survivors, nephron‐sparing surgery is always the preferred option 15,16 . MIS is appropriate only if the tumor has either a location (multiple small tumors, hilar tumor) or a volume that requires complete nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In order to preserve as much renal tissue as possible and decrease renal and cardiac morbidity for long-term survivors, nephron-sparing surgery is always the preferred option. 15,16 MIS is appropriate only if the tumor has either a location (multiple small tumors, hilar tumor) or a volume that requires complete nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In an English study, Bailey reported compensatory renal hypertrophy in 38/40 patients [41]. Neu et al detected compensatory contralateral renal hypertrophy in 88, 3% of TWs [42]. The mean percent of expected renal length in the TWs group was 118%, while in the control group, the value of expected renal length was nearly 100%.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to determine whether the absence of one kidney is a marker for CKD development [49]. In the Neu TWs study, 21/34 (62%) TWs (mean age 28.7 years, mean follow-up 24.8 years) had CKD stages I-III, based on cystatin-related eGFR [42]. The reason for those differences was the method of GFR estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation